Thalidomide for treatment of severe intestinal bleeding. Issue 4 (11th March 2004) - Bauditz, J; Schachschal, G; Wedel, S; Lochs, H
Abstract : Apart from its anti-inflammatory activity, which has been used for the treatment of active Crohn's disease, thalidomide is also a potent inhibitor of angiogenesis. We therefore studied the effect of thalidomide in six patients with severe recurrent intestinal bleeding refractory to standard treatment (three patients with Crohn's disease (CD), three patients with obscure intestinal bleeding; mean of 56 blood transfusions within the last 24 months). Bleeding stopped within two weeks after the start of thalidomide in all patients. Haemoglobin normalised without further transfusions for the whole observation period (mean follow up 33 months) while patients needed a mean of 2.2 (CD) and 3.1 (obscure bleeding) blood units/month in the 12 months before treatment. After three months of thalidomide therapy, serum levels of vascular endothelial growth factor were strongly suppressed compared with pretreatment levels. (CD 818 (82) v 129 (86) pg/ml; obscure bleeding 264 (68) v 50 (25) pg/ml). All six patients reported transient fatigue. Peripheral neuropathy was observed in one patient with CD after nine months and was reversible after lowering the dose to 100 mg daily. These results indicate that thalidomide might be useful for patients with otherwise refractory intestinal bleeding.